2010
DOI: 10.1016/j.bbamem.2009.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Light harvesting, energy transfer and electron cycling of a native photosynthetic membrane adsorbed onto a gold surface

Abstract: Photosynthetic membranes comprise a network of light harvesting and reaction center pigment-protein complexes responsible for the primary photoconversion reactions: light absorption, energy transfer and electron cycling. The structural organization of membranes of the purple bacterial species Rb. sphaeroides has been elucidated in most detail by means of polarized light spectroscopy and atomic force microscopy. Here we report a functional characterization of native and untreated membranes of the same species a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
59
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 29 publications
9
59
0
3
Order By: Relevance
“…Most likely, this is due to the upper membrane being more loosely attached to the lower membrane, which in turn adheres to the surface. Recently, it has been shown that the primary photosynthetic reactions are maintained on surface-adhered membranes (40); here, we found that proteins can reorganize on a large-scale within a membrane despite adhesion to a surface.…”
Section: Discussionsupporting
confidence: 50%
“…Most likely, this is due to the upper membrane being more loosely attached to the lower membrane, which in turn adheres to the surface. Recently, it has been shown that the primary photosynthetic reactions are maintained on surface-adhered membranes (40); here, we found that proteins can reorganize on a large-scale within a membrane despite adhesion to a surface.…”
Section: Discussionsupporting
confidence: 50%
“…Intact photosynthetic membranes have been considered as a more stable alternative to detergentpurified proteins for the generation of photocurrents. [24] Our results indicate that the use of nanodiscs may provide the best of both worlds by offering a protective membrane-like environment that is less prone to membrane damage. Under long-term storage at room temperature (20-25 8C) in the dark, membrane-embedded RCs showed complete degradation after 21 days and LDAO RCs after 100 days (Figure 5 B).…”
Section: Biophysical Characterization Of Integral Membrane Proteinsmentioning
confidence: 70%
“…[16][17][18] Inherent limitations in these systems for achieving high photocurrent magnitudes include low protein loading and light absorption. To address these issues, we have interfaced the RC-LH1 complexes with rough silver (RS), a large surface area material used for surface enhanced Raman spectroscopy (SERS) [19,20] and in emerging plasmon-enhanced solar cell technologies.…”
Section: Introductionmentioning
confidence: 99%